Pertumbuhan Perusahaan, Kebijakan Dividen, Leverage, Profitabilitas Dan Nilai Perusahaan Manufaktur Indonesia - Amira Amira; Myrna Sofia (Program Studi Manajemen Fakultas Ekonomi UMRAH, 2019)
This study aims to determine the effect of destination image, accessibility, and tourist motivation on the re-visit of marine tourism tourists in Benan Village. The influence of destination image and tourism accessibility partially on the interest of the repeat visit, the influence of the destination image and tourist accessibility simultaneously on the interest of the repeat visit. The population in this study were all marine tourism tourists in Benan Village, determining the sample using the incidental sampling method with Resco theory until 30 respondents were obtained. The data used in this study are primary data obtained from questionnaires / questionnaires. The analytical method used in this research is descriptive test, data quality test, classic assumption test, multiple linear regression analysis, and hypothesis testing. The results of the analysis in this study show that the partial image destination destination variable has a significant effect on the revisiting interest variable, the accessibility variable partially has a significant effect on the revisiting interest variable. The results of the analysis in this study indicate that the simultaneous variable of the destination image and tourism accessibility significantly influence the variable of interest in the return visit. Destination image and tourism accessibility variables in this study contributed 42.5% to the interest of re-visiting marine tourism tourists in Benan Village.